2007
DOI: 10.1002/hipo.20262
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus plays a critical role at encoding discontiguous events for subsequent declarative memory expression in mice

Abstract: The hypothesis that hippocampal activity at encoding is causally related to subsequent declarative memory expression is tested in the mouse, by using lidocaine inactivation of the hippocampus in combination with c-fos neuroimaging analysis. We employed a two-stage radial maze paradigm of spatial discrimination, which was previously shown to dissociate between declarative and nondeclarative expression of memory related to the same acquired material. In Stage 1 (encoding), mice learnt the constant location of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…In this paradigm, the age-related impairment in flexible memory expression (as revealed by stage 2 testing) was shown recently to derive from a primary STWM decline during (stage 1) learning; this STWM deficit was associated with an hypoactivity of the (hippocampo-prefrontal) declarative memory system and was believed to hinder relational encoding of individual arm experiences made during learning, into a unified LTDM representation (Mingaud et al, 2007) (our unpublished data).…”
Section: Experiments 3a and 3b: Vitamin A Supplementation Effects On mentioning
confidence: 79%
See 4 more Smart Citations
“…In this paradigm, the age-related impairment in flexible memory expression (as revealed by stage 2 testing) was shown recently to derive from a primary STWM decline during (stage 1) learning; this STWM deficit was associated with an hypoactivity of the (hippocampo-prefrontal) declarative memory system and was believed to hinder relational encoding of individual arm experiences made during learning, into a unified LTDM representation (Mingaud et al, 2007) (our unpublished data).…”
Section: Experiments 3a and 3b: Vitamin A Supplementation Effects On mentioning
confidence: 79%
“…The selective two-choice deficit is interpreted as a loss in the ability to encode individual arm experiences into a relational representation sustaining mnemonic flexibility, i.e., LTDM (Cohen and Eichenbaum, 1993;Eichenbaum, 2004), with the sparing of procedural learning capabilities relying on rigid and separate memory representations (for aged monkeys, see also Rapp et al, 1996). As demonstrated recently (Mingaud et al, 2007) and further confirmed by present Fos imaging data, mnemonic inflexibility as revealed by stage 2 testing is associated with a defect in (stage 1) learning-induced activation of hippocampal and prefrontal areas, known for subserving declarative memory.…”
Section: Hippocampal Retinoid Signaling Hypoexpression Is Associated mentioning
confidence: 99%
See 3 more Smart Citations